2013
DOI: 10.1371/journal.pone.0064859
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Afferent Mediates the Anorectic Effect of Peripheral Secretin

Abstract: Secretin (SCT) is a classical peptide hormone that is synthesized and released from the gastrointestinal tract after a meal. We have previously shown that it acts both as a central and peripheral anorectic peptide, and that its central effect is mediated via melanocortin system. As peripheral satiety signals from the gastrointestinal tract can be sent to the brain via the vagal afferent or by crossing the blood-brain barrier (BBB), we therefore sought to investigate the pathway by which peripheral SCT reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Gastric distension also activates magnocellular oxytocin neurons, probably also via activation of NTS neurons, though whether these are the same neurons as are activated by CCK is not known [39]. Both oxytocin and vasopressin neurons in the SON are also activated by systemic administration of secretin [40], a hormone secreted from the duodenum in response to food intake which regulates gastric secretion and emptying, and this again is mediated by a vagal projection to the NTS [41].…”
Section: The Magnocellular Oxytocin Systemmentioning
confidence: 99%
“…Gastric distension also activates magnocellular oxytocin neurons, probably also via activation of NTS neurons, though whether these are the same neurons as are activated by CCK is not known [39]. Both oxytocin and vasopressin neurons in the SON are also activated by systemic administration of secretin [40], a hormone secreted from the duodenum in response to food intake which regulates gastric secretion and emptying, and this again is mediated by a vagal projection to the NTS [41].…”
Section: The Magnocellular Oxytocin Systemmentioning
confidence: 99%
“…and i.p. SCT ( 39 , 46 ). In addition, it has been reported that central and peripheral SCT increased melanocortin-4 receptor (MC4R) mRNA in the PVN, and administration of MC4R antagonist, SHU9119, in the PVN reduced the anorectic effect of central and peripheral SCT, indicating the involvement of melanocortin system ( 39 , 46 ).…”
Section: Secretinmentioning
confidence: 99%
“…SCT ( 39 , 46 ). In addition, it has been reported that central and peripheral SCT increased melanocortin-4 receptor (MC4R) mRNA in the PVN, and administration of MC4R antagonist, SHU9119, in the PVN reduced the anorectic effect of central and peripheral SCT, indicating the involvement of melanocortin system ( 39 , 46 ). We previously showed that K + -induced depolarization of hypothalamic explants released SCT endogenously through voltage-gated sodium and calcium channels, suggesting that this endogenous SCT could function as a neurotransmitter in the region ( 34 , 35 ).…”
Section: Secretinmentioning
confidence: 99%
“…I.p.-SCT stimulates c-Fos expression in area prostema (AP) and NTS of the brainstem as well as ARC and PVN of the hypothalamus, and this eff ect of SCT was blocked by subdiaphragmatic vagotomy [ 34 , 38 ] . Additionally, a more recent report from our laboratory shows that subdiaphragmatic vagotomy also abolishes the anorectic eff ect of i.p.-SCT [ 39 ] . Although SCT has been shown to cross the bloodbrain barrier (BBB) [ 40 ] , these studies therefore indicate that circulating SCT does not cross the BBB to exert its anorectic eff ect.…”
Section: Secretin (Sct)mentioning
confidence: 72%